Critical Path Method Pada Proyek Konstruksi Preservasi Jalan SP. ITCHI-SP.3 Riko Segmen II Penajam Paser Utara untuk Mengendalikan Biaya dan Waktu - Aldo Dwizadana Akbar; Gede Sarya (Faculty Of Engineering University 17 August 1945 Semarang, 2023)
Abstract. Delays in project completion can be caused by ineffective project management, modifications to specifications made by planners, and delays in material procurement. SP road preservation construction project completion. ITCHI – SP. 3 Riko Segment II could be delayed as a result of alterations to piling specifications by the planner and delays in the procurement of piles. An effective and efficient network and the acceleration of project activities are required to prevent project completion delays. In this study, activities on the project's critical path are analyzed using the Critical Path Method and Microsoft Project 2013 software. The purpose of this research is to analyze the activities on the project's critical path, as well as the cost and duration of work items on the project's critical path. Additionally, the duration of the SP road preservation construction project will be analyzed. After expediting work along the critical path, ITCHI – SP. 3 Riko Segment II was completed. The original project completion time of 344 calendar days can be shortened to 240 calendar days for a fee of IDR 51,153,849,429.30. Keywords: Critical Path Method, Microsoft Project 2013, Project acceleration. Abstrak. Keterlambatan penyelesaian proyek dapat disebabkan oleh manajemen proyek yang tidak efektif, modifikasi spesifikasi yang dilakukan oleh perencana, dan keterlambatan pengadaan material. Penyelesaian proyek pembangunan preservasi jalan SP. ITCHI – SP. 3 Riko Segmen II dapat mengalami keterlambatan akibat perubahan spesifikasi tiang pancang oleh perencana dan keterlambatan pengadaan tiang pancang. Jaringan kerja yang efektif dan efisien serta percepatan kegiatan proyek diperlukan untuk mencegah keterlambatan penyelesaian proyek. Pada penelitian ini, aktivitas pada jalur kritis proyek dianalisis menggunakan Critical Path Method dan software Microsoft Project 2013. Tujuan dari penelitian ini adalah untuk menganalisis aktivitas pada jalur kritis proyek, serta biaya dan durasi item pekerjaan pada jalur kritis proyek. Selain itu, durasi proyek pembangunan preservasi jalan SP akan dianalisis. Setelah mempercepat pekerjaan di sepanjang jalur kritis, ITCHI – SP. 3 Riko Segmen II selesai. Waktu penyelesaian proyek yang semula 344 hari kalender dapat dipersingkat menjadi 240 hari kalender dengan biaya Rp 51.153.849.429,30. Kata Kunci: Critical Path Method, Microsoft Project 2013, Percepatan Proyek